Application Of Transformer Diagnostic Application To Improve Students' Analytical Skills In Transformer Courses Of Electrical Engineering D4 Program - Sidik Sidin, Udin; Prasojo, Kholik; Irfan, Muhammad; Suhartono, Suhartono (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study aimed to address the prevalent difficulty among electrical engineering students in applying theoretical knowledge to the practical interpretation of transformer diagnostic data. The primary objective was to assess the effectiveness of a purpose-built diagnostic software application in improving the analytical skills required for this task. Method: The research employed a quasi-experimental, one-group pretest-posttest design involving a sample of 36 undergraduate students in a D4 Electrical Engineering program. Participants' analytical skills were measured before and after the intervention, which consisted of training with the diagnostic application. Data were collected through quantitative tests, student perception surveys, and instructor observation sheets. The analysis involved paired sample t-tests and N-Gain calculations, with findings triangulated using qualitative feedback to enhance validity. Result: The intervention yielded highly positive outcomes, demonstrating a statistically significant improvement in students' analytical abilities. The mean score rose from 56.19 to 82.58, and an average N-Gain score of 0.61 classified the application's effectiveness in the